Community Development and Microcredit: Proposing an Analytical Framework for Social Innovation Ecosystems - Castelo, Joelma Leite; Santos, Sandra Maria dos; Silva Filho , José Carlos Lázaro da; Silva, Clayton Robson Moreira da (Organizações & Sociedade, 2025)
This study proposes an analytical framework for community social innovation ecosystems, based on empirical insights from community development and microcredit projects. Using a qualitative, exploratory descriptive approach, the research examines a case study of 38 beneficiaries of Banco do Nordeste do Brasil S.A.’s Microcredit Program – Crediamigo, based in Bom Jardim, a region with low HDI in the Brazilian state of Ceará. This study identifies key elements of social innovation for community development, organized into three dimensions: motivation, processes, and social action. Additionally, it highlights barriers that hinder the diffusion of social innovation. Furthermore, the study assesses the scope, typology, and depth of social innovation generated by microentrepreneurs. The findings reveal the dynamics of actors at a micro level within analytical structures from both process and output perspectives, highlighting the importance of an ecosystemic approach to understanding better the interactions among social actors and innovative resource management. This study offers empirical-theoretical contributions by advancing our understanding of social innovation dynamics within local communities and social organizations and emphasizing the role of intersectoral partnerships in addressing vulnerabilities and social inequalities. By systematizing a framework that integrates the processes and outputs of social innovation initiatives, the study provides a tool to foster the social innovation ecosystem.